KADAR PROTEIN URIN PADA IBU HAMIL TRIMESTER II DAN III DI PUSKESMAS II DENPASAR BARAT - Wayan Merta (Meditory : The Journal of Medical Laboratory, 2017)
ABSTRACT The presence of excess level of protein in pregnant women’s urine is one of the cause of preeclampsia, besides hypertension and edema. Some disease that can discover protein in pregnant women’s urine are renal diseases (glomerulus or tubular disease) and non-renal diseases (heart disease, liver disease, fever, stress, diabetes militus, hypertenssion). This study aims at describing the result of proteinuria level based on the examination from pregnant women’s urine of second and third trimester in Puskesmas II Denpasar Barat. This research applied a descriptive survey and the amount of samples was taken by using non-probability sampling method with insidental sampling technique, the data were collected from 39 respondents during the period of February to May 2016.The sample were examined semi-quantitatively by using dipstick test. Results of the examination to 39 samples indicates that 29 urine samples (74,36%) was negative, seven urine samples (17,95%) positive 1 (+), two urine samples (5,13%) positive 2 (++) and one urine samples (2,56%) positive 3 (+++). keywords: pregnant woment; protein urine level; second trimester; third trimester